Ars litterarum o la conformación artística de un idioma - Quirós R., Manuel Antonio (2004)
Any literature is based upon its respective language. This paper states how a language is to be used for its artistic creation in writing, which, in strict sense, is named Iiterature. The Ars Litterarum, to wit, the good literature, is an art and as such, it needs gramatical and stylistic resources of its language. Based upon the Greco-Latin culture, specially, its terminology, it is hereby explained how a writing becomes literature: with inspiration and the fulfilling of the rules of the elocutio. For that purpose, the paper takes in con sideratio n the fine arts, its mean, schools and aim, aesthetics, literary style and ornatus. There are not absent a personal definition of "literature", some greek etymologies, some definitions in latin language and so me c1assical and romance examples.